Diagnostic yield of 18F‐FDG PET/CT imaging and urinary CXCL9/creatinine levels in kidney allograft subclinical rejection. Issue 5 (3rd January 2020) - Hanssen, Oriane; Weekers, Laurent; Lovinfosse, Pierre; Jadoul, Alexandre; Bonvoisin, Catherine; Bouquegneau, Antoine; Grosch, Stéphanie; Huynen, Alexandre; Anglicheau, Dany; Hustinx, Roland; Jouret, Francois
Abstract : Subclinical kidney allograft acute rejection (SCR) corresponds to "the unexpected histological evidence of acute rejection in a stable patient." SCR detection relies on surveillance biopsy. Noninvasive approaches may help avoid biopsy‐associated complications. From November 2015 to January 2018, we prospectively performed positron emission tomography/computed tomography (PET/CT) after injection of F 18 ‐fluorodeoxyglucose ( 18 F‐FDG) in adult kidney transplant recipients with surveillance biopsy at ~3 months posttransplantation. The Banff‐2017 classification was used. The ratio of the mean standard uptake value (mSUVR) between kidney cortex and psoas muscle was measured. Urinary levels of CXCL‐9 were concomitantly quantified. Our 92‐patient cohort was categorized upon histology: normal (n = 70), borderline (n = 16), and SCR (n = 6). No clinical or biological difference was observed between groups. The mSUVR reached 1.87 ± 0.55, 1.94 ± 0.35, and 2.41 ± 0.54 in normal, borderline, and SCR groups, respectively. A significant difference in mSUVR was found among groups. Furthermore, mSUVR was significantly higher in the SCR vs normal group. The area under the receiver operating characteristic curve (AUC) was 0.79, with 83% sensitivity using an mSUVR threshold of 2.4. The AUC of urinary CXCL‐9/creatinine ratios comparatively reached 0.79. The mSUVR positively correlated with ti and acute composite Banff scores. 18 F‐FDG‐PET/CT helps noninvasively exclude SCR, with a negative predictive value of 98%. External validations are required. Abstract : Positron‐emission tomography following the intravenous injection of 18 F‐fluorodeoxyglucose helps rule out subclinical rejection in kidney transplant recipients.